Aerobiological study of anemophilous pollens in the city of Toluca, Mexico - María de la Luz Cid del Prado-Izquierdo; Berenice Piedras-Gutiérrez; Ángel Visoso-Salgado; Martín Becerril-Ángeles (Revista Alergia México, 2015)
Background: Due to the high incidence of allergic diseases in Mexico, caused by exposure to pollens, there have been several studies of plants and atmospheric pollens in various regions in the last decades. In the city of Toluca there have been two previous pollen samplings using gravimetric methodology, for which it is necessary to obtain new samplings with a standardized volumetric technique, in order to have updated and confident results of a region with considerable environmental changes in the last years.